2015
DOI: 10.1097/jpn.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Distress in Pregnancy

Abstract: Gastrointestinal discomforts are a very common complaint in pregnancy. In fact, most pregnant women will experience at least one discomfort. This article focuses on 5 common conditions that occur in pregnancy: gastroesophageal reflux disease, diarrhea, constipation, hemorrhoids, and pica. While these conditions do occur in men and nonpregnant women, they occur more frequently in pregnancy because of the anatomic and physiologic changes associated with gestation. The type and severity of symptoms can vary from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 36 publications
(83 reference statements)
1
13
0
4
Order By: Relevance
“…All these factors may add up to the smooth muscle relaxing effects of progesterone to cause constipation which is considered as one of the five causes of gastrointestinal distress in pregnant population. 18 There appeared to be a significant association between parity and occurrence of haemorrhoids from in this study, close to one third of the respondents indicated the symptom from the survey, similar figure had been quoted from another study by Longo et al with raised blood volume and intraabdominal pressure exerted by the growing uterus, as well as the relaxing effects of circulating progesterone as the possible risk factors for the development of haemorrhoids. 19 Others had alluded to the high vascularity of the perianal vessels, but the symptoms are commoner in the last part of pregnancy and could persist even after delivery with significant life sequelae.…”
Section: Discussionsupporting
confidence: 88%
“…All these factors may add up to the smooth muscle relaxing effects of progesterone to cause constipation which is considered as one of the five causes of gastrointestinal distress in pregnant population. 18 There appeared to be a significant association between parity and occurrence of haemorrhoids from in this study, close to one third of the respondents indicated the symptom from the survey, similar figure had been quoted from another study by Longo et al with raised blood volume and intraabdominal pressure exerted by the growing uterus, as well as the relaxing effects of circulating progesterone as the possible risk factors for the development of haemorrhoids. 19 Others had alluded to the high vascularity of the perianal vessels, but the symptoms are commoner in the last part of pregnancy and could persist even after delivery with significant life sequelae.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, treatment of heartburn and reflux results in improved PUQE scores and quality of life scores (Gill et al, 2009a). Antacids containing aluminum or calcium are recommended as first-line of treatment during pregnancy for acid reflux and heartburn and can be used to treat women with NVP considering that these drugs were not found to be teratogenic (Law et al, 2010; Mahadevan, 2007; Zielinski et al, 2015). Histamine-2 receptor antagonists such as ranitidine (Zantac) or famotidine (Pepcid) are another treatment option if antacids are no longer working.…”
Section: Treatmentmentioning
confidence: 99%
“…Histamine-2 receptor antagonists such as ranitidine (Zantac) or famotidine (Pepcid) are another treatment option if antacids are no longer working. These drugs are considered safe (category B) to treat acid reflux and/or heartburn in women with NVP (Gill et al, 2009c; Gill et al, 2009d; Zielinski et al, 2015). Several studies to date indicate that proton pump inhibitors are most likely safe in pregnancy, although omeprazole (Prilosec) is classified as a category C drug because its use in early pregnancy may increase the risk of birth defects (Zielinski et al, 2015).…”
Section: Treatmentmentioning
confidence: 99%
“…Sin embargo, la visualización de tumores colorrectales por ecografía es difícil. No obstante, la sensibilidad para detectar metástasis hepáticas es de 75% (9) . La resonancia magnética es más útil para detectar con precisión los cambios patológicos en colon e hígado.…”
Section: T4bunclassified